2018
DOI: 10.1212/wnl.0000000000005678
|View full text |Cite
|
Sign up to set email alerts
|

Use of medical care biases associations between Parkinson disease and other medical conditions

Abstract: Use of care should be considered when evaluating associations between PD and other medical conditions to ensure that positive associations are not attributable to bias and that inverse associations are not masked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…We also examined the effect of adjustment for several individual level variables, including use of medical care. We adjusted for use of medical care because we previously found that greater use of care is associated with a greater PD case ascertainment in the present study and can bias associations [60]. In the present analysis, our concern was that use of medical care could be a nuisance mediator.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We also examined the effect of adjustment for several individual level variables, including use of medical care. We adjusted for use of medical care because we previously found that greater use of care is associated with a greater PD case ascertainment in the present study and can bias associations [60]. In the present analysis, our concern was that use of medical care could be a nuisance mediator.…”
Section: Discussionmentioning
confidence: 94%
“…We estimated the probability (0% to 100%) of "ever smoking" tobacco using a multifaceted approach [42,60]. We assigned a probability of 100% to any beneficiary with a diagnosis or procedure code specific to tobacco use, primarily ICD-9 305.1 (tobacco use disorder) or ICD-9 V15.82 (history of tobacco use).…”
Section: Determination Of Covariatesmentioning
confidence: 99%
“…A limitation of studies evaluating the associations between two conditions is that patients diagnosed with one condition have higher health services utilization than healthy individuals and may subsequently be more likely to be diagnosed with another condition 64 . No study included in our systematic review accounted for increased health care use.…”
Section: Discussionmentioning
confidence: 99%
“…Even in combination, these four codes are not sufficiently sensitive to characterize tobacco smoking history accurately. 9, 10 Therefore, we created and validated a smoking variable as the probability of having ever smoked based on sex, race/ethnicity, birth cohort, and > 600 ICD-9 and CPT codes including the above tobacco-specific codes and 17 other medical conditions. 2 We estimated this probability with a logistic regression model that we developed from Behavioral Risk Factor Surveillance System (BRFSS) survey data from a population-based sample of Medicare-aged respondents.…”
Section: Methodsmentioning
confidence: 99%